2014
DOI: 10.1371/journal.pone.0113707
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Osteophytic, Chondral, and Subchondral Structures in a Surgically-Induced Osteoarthritis Rabbit Model

Abstract: ObjectiveThis study aimed to assess changes in osteophytic, chondral, and subchondral structures in a surgically-induced osteoarthritis (OA) rabbit model in order to correlate MRI findings with the macroscopic progress of OA and to define the timepoint for disease status in this OA model.MethodsThe OA model was constructed by surgery in thirty rabbits with ten normal rabbits serving as controls (baseline). High-resolution three-dimensional MRI using a 1.5-T coil was performed at baseline, two, four, and eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…MRI is able to accurately detect the progression of cartilage lesions and subchondral bone edema over an eight-week period ( 13 ). In the present study, this quantitative MRI technique was used to measure the thickness of cartilage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI is able to accurately detect the progression of cartilage lesions and subchondral bone edema over an eight-week period ( 13 ). In the present study, this quantitative MRI technique was used to measure the thickness of cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of radiological joint space narrowing by X-ray radiography is the ‘gold standard’ for assessing OA, while there is currently no well-established imaging modality to visualize and quantify changes in chondral and subchondral tissue ( 13 ). MRI, with superior soft tissue contrast, is the best technique available for the assessment of normal articular cartilage and cartilage lesions ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI has also been used to acquire 3D images of cartilage volume loss in a naturally occurring OA caused by obesity in the guinea pig model [ 245 ]. Some surgical models which induce OA and have used MRI to study changes include ACLT and Medial Meniscus Tear [ 244 , 246 ]. In much smaller animal models such as mice, standard MRI measurements are not possible; however, micro-MRI has been utilized to study ACLT induced OA [ 247 ] and in Brtl mouse models [ 248 ].…”
Section: Measures Of Disease Outcomementioning
confidence: 99%
“…For example, Jia et al performed an MRI analysis of OA in rabbit models, and they noted that at as little as 8 weeks, cartilage defects, subchondral bone lesions, and osteophyte size significantly progressed (p < 0.05). 23 In addition, Crema et al through the Multicenter Osteoarthritis Study observed that worsening of cartilage damage was more frequently observed than meniscal damage, with an associated increased risk in joint space narrowing. 24 Furthermore, additional assessments showed a decrease in the size of a large cartilage blister, the near complete filling of a small full-thickness cartilage defect, an increase in cartilage thickness in a large defect and remodeling of the underlying bone.…”
Section: Discussionmentioning
confidence: 99%